DETERMINATION OF CAPECITABINE AND ITS ACTIVE METABOLITE 5-FLUOROURACIL IN BLOOD PLASMA BY HPLC-MS/MS - E. S. Melnikov; I. E. Shohin; A. A. Aksenov; G. V. Adamov; A. N. Konyushkova (Разработка и регистрация лекарственных средств)
A method for quantification of capecitabine and 5-fluorouracil in human plasma was developed. The sample preparation was carried out by protein precipitation with methanol. The quantitative determination was performed by HPLC with a triple quadrupole mass-detector. The method was validated in terms of selectivity, calibration curve, accuracy, precision, lower limit of quantification, and stability. The analytical range was 10.0-20000.0 ng/mL for capecitabine and 10.0-400.0 ng/ml for 5-fluorouracil. The developed method may be used for bioequivalence studies of capecitabine drug products.